Pembuktian Terbalik Dalam Perkara Tindak Pidana Korupsi Ditinjau Dari Asas Praduga Tidak Bersalah (Presumption of Innocence) - Bayu Dwi Putra; Muhammad Hendri Yanova (Jurnal Penegakan Hukum Indonesia, 2022)
This study aims to examine and analyze the regulation and application of the reverse evidence system in the Corruption Eradication Act. This research is a normative legal research, the nature of prescriptive research is to re-examine according to legal theory against norms that are considered still unclear. The results of this study indicate that the regulation of reverse proof of corruption begins with Law Number 3 of 1971 concerning the Eradication of Criminal Acts of Corruption which has explicitly included it in Article 17. In its development, Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption also regulates the reverse evidence, namely in Article 37. However, the policy in the formulation of the reversed evidence has not been able to represent the circumstances and situations in handling corruption crimes at that time where corruption was an extraordinary crime that had caused financial losses. country. The issuance of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes provides a clearer policy direction than the previous law, namely by improving the formulation of reverse evidence. The implication of the reverse proof system with this change is that there are two types of reverse proof systems contained in the law on eradicating corruption, namely balanced limited reverse proof and pure/full reverse proof.